Analisis Ornamen Kerawang Gayo Pada Rumah Adat Pitu Ruang Kabupaten Aceh Tengah - Mahara Mahara; Misgiya Misgiya (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
This research aims to describe Gayo Filigree Ornaments from indicators of shape, clor, meaning and placement carried out in the traditional house of Pitu Ruang. This research is a qualitative descriptive study. The subjects of this study were 10 motifs gayo filigree ornaments namely emun motif set off (Cloud parade), Puter Rope (Rotate Rope), Pucuk Ni Tuis (Bamboo Shoots), Emun Beriring, Tekukur, Bintang Ulen (Stars and Moon), Ulen-Ulen (Moon Flower), Bunge Ni Terpuk (Kuncung Flower), Bunge Kemang (Flower flower) and Emun Berkune. The accuracy of shapes, colors, meanings, and placements became objects in this study. The data collection methods used are observation, documentation, and interviews. The data analysis used is a qualitative descriptive analysis technique. The results of this study show that the accuracy of the shape, color, meaning and placement of Gayo Filigree Ornaments in the traditional house of Pitu Ruang is in accordance with the original form. All motifs contained in the traditional house of Pitu Ruang have meaning related to the life of gayo people in their daily lives, and the placement in the traditional house of Pitu Ruang has also been appropriately placed.